2018
DOI: 10.2903/j.efsa.2018.5376
|View full text |Cite
|
Sign up to set email alerts
|

Peer review of the pesticide risk assessment for the triazole derivative metabolites in light of confirmatory data submitted

Abstract: The conclusions of EFSA following the peer review of the initial risk assessment carried out by the competent authority of the rapporteur Member State, the United Kingdom, for the pesticide risk assessment for the triazole derivative metabolites are reported. The context of the peer review was that requested by the European Commission following the submission and evaluation of confirmatory data in relation to mammalian toxicology, metabolism and residue data. The conclusions were reached on the basis of the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(127 citation statements)
references
References 2 publications
6
121
0
Order By: Relevance
“…The proposed Codex MRLs for post‐harvest uses are not acceptable because the toxicity of metabolite R014821 (formed after post‐harvest treatment) is not sufficiently addressed. This recommendation is in line with the recommendations derived in the recently published reasoned opinions of EFSA (, o) which were supported by MS in a MS consultation…”
Section: Comments On Jmpr Report Chapter 5 (Individual Substances Asssupporting
confidence: 89%
See 1 more Smart Citation
“…The proposed Codex MRLs for post‐harvest uses are not acceptable because the toxicity of metabolite R014821 (formed after post‐harvest treatment) is not sufficiently addressed. This recommendation is in line with the recommendations derived in the recently published reasoned opinions of EFSA (, o) which were supported by MS in a MS consultation…”
Section: Comments On Jmpr Report Chapter 5 (Individual Substances Asssupporting
confidence: 89%
“…In 2018, EFSA concluded that insufficient data are available to conclude on the toxicological profile of metabolites formed in plants after post‐harvest treatment (R014821) and observed in animal metabolism (FK‐772 and FK‐284) (EFSA, , o). In the EU evaluation, one study for metabolite R14821 and one study for metabolite FK772 was considered to give equivocal results, as the findings did not comply to either negative or positive outcome as defined in the respective OECD guidelines.…”
Section: Comments On Jmpr Report Chapter 5 (Individual Substances Assmentioning
confidence: 99%
“…EFSA has based its assessment on the PROFile submitted by the RMS, the evaluation report accompanying the PROFile (United Kingdom, 2011), the draft assessment report (DAR) and its addenda prepared under Council Directive 91/414/EEC (United Kingdom, 2005, 2009a, the conclusion on the peer review of the pesticide risk assessment of the active substance fenbuconazole (EFSA, 2010), the Joint Meeting on Pesticide residues (JMPR) Evaluation report (FAO, 2009(FAO, , 2013, as well as the evaluation reports submitted during the completeness check (EURL, 2016, France, 2016, 2017Italy, 2016Italy, , 2017Portugal, 2016;Spain, 2016;United Kingdom, 2016, 2017. The assessment is performed in accordance with the legal provisions of the uniform principles for evaluation and authorisation of plant protection products as set out in Commission Regulation (EU) No 546/2011 11 and the currently applicable guidance documents relevant for the consumer risk assessment of pesticide residues (European Commission, 1997a-g, 2000, 2010a,b, 2016bOECD, 2011OECD, , 2013.…”
Section: Assessmentmentioning
confidence: 99%
“…To assess the magnitude of fenbuconazole residues resulting from the reported GAPs, EFSA considered all residue trials reported by the RMS in its evaluation report (United Kingdom, 2011), including residue trials evaluated in the framework of the peer review (EFSA, 2010) and additional data submitted during the completeness check (France, 2016(France, , 2017Italy, 2016Italy, , 2017Portugal, 2016;Spain, 2016;United Kingdom, 2016, 2017. Residue trial samples considered in this framework were stored in compliance with the demonstrated storage conditions with the exception of northern European samples for apples, pears, table and wine grapes where storage information was not provided.…”
Section: Magnitude Of Residues In Primary Cropsmentioning
confidence: 99%
See 1 more Smart Citation